Pengaruh Latihan Pergelangan Tangan terhadap Kemampuan Pukulan Forehand Tenis Meja pada Siswa SMA Negeri 1 Pematang Siantar - Ferdinandus Simbolon; Marwadinur Marwadinur; Josua Jumagar Situmorang; Brian Putra Hasudungan Sitompul (Jurnal Keluarga Sehat Sejahtera, 2026)
This study aimed to determine the effect of wrist training on the forehand stroke ability of students at SMA Negeri 1 Pematang Siantar. The research employed an experimental method with a quantitative approach using a One Group Pretest-Posttest Design. The population consisted of students participating in table tennis activities at SMA Negeri 1 Pematang Siantar, while the sample comprised 20 students selected through purposive sampling. The research instrument was a forehand stroke ability test administered before (pretest) and after (posttest) the treatment. The treatment consisted of wrist training exercises conducted for six weeks with a frequency of three sessions per week. Data were analyzed using the paired sample t-test to determine the effect of the training on forehand stroke performance. The results showed that the mean pretest score of 58.40 increased to 74.20 in the posttest, indicating an improvement of 15.80 points or 27.05%. The hypothesis testing revealed that the calculated t-value (8.72) was higher than the t-table value (2.093) at a significance level of 5%. Therefore, it can be concluded that wrist training has a significant effect on improving the forehand stroke ability of students at SMA Negeri 1 Pematang Siantar.